LGBTQI Inclusive Cancer Care: A Discourse Analytic Study of Health Care Professional, Patient and Carer Perspectives - Ussher, Jane M.; Power, Rosalie; Perz, Janette; Hawkey, Alexandra J.; Allison, Kimberley (Frontiers in Oncology, 2022)
Background: Awareness of the specific needs of LGBTQI cancer patients has led to calls for inclusivity, cultural competence, cultural safety and cultural humility in cancer care. Examination of oncology healthcare professionals’ (HCP) perspectives is central to identifying barriers and facilitators to inclusive LGBTQI cancer care. Study Aim: This study examined oncology HCPs perspectives in relation to LGBTQI cancer care, and the implications of HCP perspectives and practices for LGBTQI patients and their caregivers. Method: 357 oncology HCPs in nursing (40%), medical (24%), allied health (19%) and leadership (11%) positions took part in a survey; 48 HCPs completed an interview. 430 LGBTQI patients, representing a range of tumor types, sexual and gender identities, age and intersex status, and 132 carers completed a survey, and 104 LGBTQI patients and 31 carers undertook an interview. Data were analysed using thematic discourse analysis. Results: Three HCP subject positions – ways of thinking and behaving in relation to the self and LGBTQI patients – were identified:‘Inclusive and reflective’ practitioners characterized LGBTQI patients as potentially vulnerable and offered inclusive care, drawing on an affirmative construction of LGBTQI health. This resulted in LGBTQI patients and their carers feeling safe and respected, willing to disclose sexual orientation and gender identity (SOGI) status, and satisfied with cancer care. ‘Egalitarian practitioners’ drew on discourses of ethical responsibility, positioning themselves as treating all patients the same, not seeing the relevance of SOGI information. This was associated with absence of LGBTQI-specific information, patient and carer anxiety about disclosure of SOGI, feelings of invisibility, and dissatisfaction with healthcare. ‘Anti-inclusive’ practitioners’ expressed open hostility and prejudice towards LGBTQI patients, reflecting a cultural discourse of homophobia and transphobia. This was associated with patient and carer distress, feelings of negative judgement, and exclusion of same-gender partners. Conclusion: Derogatory views and descriptions of LGBTQI patients, and cis-normative practices need to be challenged, to ensure that HCPs offer inclusive and affirmative care. Building HCP’s communicative competence to work with LGBTQI patients needs to become an essential part of basic training and ongoing professional development. Visible indicators of LGBTQI inclusivity are essential, alongside targeted LGBTQI cancer resources and information.